Gleaner, fisher, trader, processor: understanding gendered employment in fisheries and aquaculture - Nireka Weeratunge; Katherine A Snyder; Choo Poh Sze (Blackwell Publishing, 2025)
Most research on gender difference or inequities in capture fisheries and aquaculture in Africa and the Asia-Pacific focuses on the gender division of labour. Emerging research on globalization, market changes, poverty and trends in gendered employment within this sector reveals the need to move beyond this narrow perspective. If gleaning and post-harvesting activities were enumerated, the fisheries and aquaculture sector might well turn out to be female sphere. A livelihoods approach better enables an understanding of how employment in this sector is embedded in other social, cultural, economic, political and ecological structures and processes that shape gender inequities and how these might be reduced. We focus on four thematic areas – markets and migration, capabilities and well-being, networks and identities, governance and rights – as analytical entry points. These also provide a framework to identify research gaps and generate a comparative understanding of the impact of development processes and socioecological changes, including issues of climate change, adaptation and resilience, on gendered employment. Without an adequate analysis of gender, fisheries management and development policies may have negative effects on people’s livelihoods, well-being and the environment they depend on, or fail altogether to achieve intended outcomes.